Degradation of 17β-estradiol by Novosphingobium sp. ES2-1 in aqueous solution contaminated with tetracyclines. (May 2020) - Li, Shunyao; Liu, Juan; Sun, Kai; Yang, Zhiyao; Ling, Wanting
Abstract: 17 β -estradiol (E2) often coexists with tetracyclines (TCs) in wastewater lagoons at intensive breeding farms, threatening the quality of surrounding water bodies. Microbial degradation is vital in E2 removal, but it is unclear how TCs affect E2 biodegradation. This primary study investigated the mechanisms of E2 degradation by Novosphingobium sp. ES2-1 in the presence of TCs and assessed the removal efficiency of E2 by strain ES2-1 in natural waters containing TCs. E2 biodegradation was unaffected at TCs concentrations below 0.1 mg L −1 yet significantly inhibited at TCs above 10 mg L −1 . As elevation of TCs, E2 biodegradation rate constant decreased, and the biodegradation kinetics equation gradually deviated from the pseudo-first-order dynamics model. Importantly, the presence of TCs, especially at high-level concentrations, significantly hindered E2 ring-opening process but promoted the condensation of some phenolic ring-opening products with NH3, thereby increasing the abundance of pyridine derivatives, which were difficult to decompose over time. Additionally, strain ES2-1 could remove 52.1–100% of nature estrogens in TCs-contaminated natural waters within 7 d. Results revealed the mechanisms of TCs in E2 biodegradation and the performance of a functional strain in estrogen removal in realistic TCs-contaminated aqueous solution. Graphical abstract: Image 1 Highlights: E2 biodegradation was significantly disturbed at elevated TCs concentrations. TCs hydrolysis happened simultaneously with E2 biodegradation. TCs disturbed the cleavage of E2, reducing the abundance of ring-opening products. TCs enabled E2 metabolism to linger in the stage of condensing with NH3 . Strain ES2-1 could effectively remove E2 in natural waters containing TCs. Abstract : TCs may inhibit the E2 degradation by strain ES2-1, and disturb the cleavage of E2, reducing the abundance of ring-opening products.